Indonesia-Singapore Diplomatic Relations: Exploring His-torical Ties, Economic Cooperation, Security, and Legal Challenges in All Aspects - A. Junaedi Karso (International Journal of Humanities and Social Sciences Reviews, 2025)
The relationship between Indonesia and Singapore has deep historical roots, tracing back to the ancient kingdoms. In the 7th century, the Strait of Singapore was part of the Srivijaya Empire. Later, in 1365, the Javanese hymn Nagarakretagama, written during the Majapahit era, mentioned a settlement on the island called Temasek, highlighting the long-standing connection between the two regions. Trade between Indonesia and Singapore has grown significantly over the years, reaching S$36 billion (US$29.32 billion), with Singapore being the largest foreign investor in Indonesia, having invested US$1.14 billion across 142 projects. Additionally, trade between the two nations surged to approximately $68 billion in 2010, with Indonesia's non-oil and gas exports to Singapore reaching their highest levels. The two countries have established robust cooperation in various sectors, including tourism, security, counter-terrorism, and environmental concerns. However, the relationship is not without its challenges. One significant issue is Singapore's role as a haven for Indonesian corruptors, with many fugitives from corruption cases seeking refuge there. This has led to tensions, particularly regarding the extradition of individuals convicted of corruption. To address these challenges, both nations must enhance the implementation of bilateral agreements, especially in political and security matters. There is a need to accelerate the technical finalization of military training areas as part of the defense cooperation agreement. Additionally, executing the extradition agreement and updating the memorandum of understanding between the Attorneys General of both countries would be crucial steps in addressing these issues and improving bilateral relations. In conclusion, while Indonesia-Singapore relations are multifaceted, with both cooperation and challenges, mutual commitment to resolving issues through diplomatic and legal means will be key to strengthening their ties in the future.